Capacity Building Strategy for Village Apparatus: Elevating Village Status of Underdeveloped Villages in Pandeglang Regency - Asropi; Laila, Nur; Riani, Putri; Larasati, Agnes; Azahra, Audrey Dhea (KnE Social Sciences, 2025)
The 2023 Village Development Index (IDM) indicates that 4,382 villages in Indonesia remain underdeveloped. Strengthening the capacity of village apparatus is crucial to fostering sustainable development and achieving independent and innovative villages. This study analyzes the capacity of village apparatus in underdeveloped villages and formulates strategies to enhance their effectiveness in the Pandeglang Regency. A qualitative research approach was employed, utilizing the Focus Group Discussion (FGD) method, and data were collected through observation, document review, and discussions with selected informants. The findings reveal that efforts to develop the competence and capacity of village apparatus remain suboptimal. Technical training does not fully address managerial and technical competency needs due to the absence of a clear competency framework. Additionally, limited initiative from village governments further hampers capacity-building efforts. To address these challenges, this study recommends the adoption of collaborative governance for more effective training, the implementation of Training Needs Analysis to align training programs with village apparatus needs, and the promotion of training programs by relevant ministries to support the achievement of Sustainable Development Goals (SDGs) at the village level.